The Impact of IL-17A Inhibition in Rheumatic and Musculoskeletal Diseases: Current Insights and Future Prospects - Sofia Ramiro; Georg Schett; Helena Marzo-Ortega; Wolfgang A. Schmidt (Rheumatology and Therapy)
Abstract Interleukin-17A (IL-17A) plays a pivotal role in many rheumatic immune-mediated inflammatory diseases. Targeting the IL-17 pathway has transformed the way psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA) are managed, with a number of IL-17A inhibitors now available for treating rheumatic and musculoskeletal diseases. This narrative review will describe the opportunities presented by novel imaging techniques in understanding the metabolic and mechanical changes that characterize the pathogenesis of PsA and axSpA. It will look at the current consensus definitions of early disease in PsA and axSpA, present evidence for the benefit of early treatment, and highlight the gaps in current knowledge. Finally, it will describe novel treatment targets to address the unmet needs in giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) and discuss the potential role of IL-17A inhibition in treating GCA and PMR.